Birthday present - Stock, Catherine (Bradbury Press ; Collier Macmillan Canada ; Maxwell Macmillan International Pub. Group, 1991)
Although he is not pleased with his mother's choice of gift for him to take to a birthday party, a little boy attends and experiences a pleasant surprise.